A Study on Game Localization Translation from the Perspective of Communicative Translation Theory: A Case Study of Black Myth: Wukong - Ye Wang (Journal of Linguistics and Communication Studies, 2025)
With China’s increasing cultural influence in the global market, video game localization has become essential in ensuring accessibility and cultural authenticity. As China’s first AAA single-player game, Black Myth: Wukong presents unique localization challenges due to its rich cultural and narrative elements. This study applies Communicative Translation Theory (CTT) to analyze its English localization, focusing on translating character names, in-game achievements, and dialogues. Using qualitative textual analysis, the research evaluates strategies such as adaptation, simplification, and idiomatic rendering. Findings reveal both effective localization techniques and areas to be improved, offering insights for refining Chinese video game localization strategies.